2005
DOI: 10.1212/01.wnl.0000148604.77591.67
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the safety and immunogenicity of synthetic Aβ42 (AN1792) in patients with AD

Abstract: AN1792 + QS-21 elicited a positive antibody response to Abeta42 in more than half of this elderly study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
238
0
6

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 328 publications
(259 citation statements)
references
References 25 publications
4
238
0
6
Order By: Relevance
“…5). As mentioned above, recent analysis of data from the AN-1792 clinical trial has produced encouraging results including demonstration of a reduction in plaque load and attenuation of cognitive decline in vaccinated AD patients who produced high titers of anti-Aβ antibodies [28,29,33]. On the other hand, Th1, but not Th2 type of immune response in vaccinated AD patients has been implicated in cell-mediated autoimmune response resulted in meningoencephalitis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5). As mentioned above, recent analysis of data from the AN-1792 clinical trial has produced encouraging results including demonstration of a reduction in plaque load and attenuation of cognitive decline in vaccinated AD patients who produced high titers of anti-Aβ antibodies [28,29,33]. On the other hand, Th1, but not Th2 type of immune response in vaccinated AD patients has been implicated in cell-mediated autoimmune response resulted in meningoencephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the adverse events (meningoencephalitis) in the AN-1792 clinical trial, follow up studies demonstrated that strong anti-Aβ antibody responses, rather than autoimmune T cell responses generated in AD patients, were capable of reducing AD pathology and diminishing the progressive cognitive decline associated with the disease [24,[28][29][30][31][32][33]. More specifically, published data from AN-1792 clinical trials suggest that the aseptic meningoencephalitis may have been caused by a T cell-mediated autoimmune response, whereas production of high titers of anti-Aβ antibodies may have been therapeutic to the AD patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations